(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Scientific and methodological foundations for processing data on personnel in universities based on the use of neural networks, fuzzy inference models, knowledge bases, and databases have been developed. Methods for forming fuzzy rule bases, modeling membership functions and linguistic terms, synthesizing components of neuro-fuzzy networks are proposed. Inference algorithms have been tested on the example of various functions that reflect the nonlinear input-output dependencies of neuro-fuzzy networks. The results are implemented in the form of data processing software modules.